A Practical Guide to Working with Sex Offenders - Wills, Diane (Jessica Kingsley Publishers, 2020)
Intro -- A Practical Guide to Working with Sex Offenders -- Cover -- Of related interest -- Title Page -- Copyright -- Contents -- Introduction -- 1. A Brief History of Sex -- Sexual behaviour -- Biology -- Sex, sexology and sexuality -- Sex and gender -- 2. Sex and Sexuality -- Sex, love, power and sexuality -- The portrayal of sex -- 3. Theories of Sexual Offending -- Why do they do it? -- Treatment -- 4. People Who Sexually Harm Others -- Typologies -- Offending against children -- Sexual violence -- Female perpetrators -- Stalking -- Mental illness -- Harmful sexual behaviour by young people -- Older people -- 5. Theories of Risk -- The risk society -- Probability -- Perceptual bias, likelihood and complexity thinking -- Defensive, defensible, precautionary principle and false positives -- Prior assumptions and Bayesian inference -- 6. Assessing the Risk of Those Who Cause Sexual Harm -- Organizational defensive and professional defensible decision-making -- Using risk assessment 'tools' -- 7. Legal Contexts -- Prosecutions -- Consent -- Sentencing -- Civil orders -- Children and young people -- Mental health -- 8. Approaches and Debates -- Treat, cure or control? From theory to practice and from practice to effective outcomes -- A brief history of interventions -- The rise of evidence-based practice -- Control, treat and correct -- Cognitive behavioural approaches -- Programm-ization -- Empathy -- Adverse childhood experiences and DESISTANCE -- 9. The Reflective Professional -- Promoting positive change to reduce the risk of future harm -- Professional values and personal change -- A person-centred approach -- Thinking critically about complex behaviours -- Looking after ourselves -- References -- Appendix: List of Sexual Offences (Sexual Offences Act 2003) and Recorded Number of Sexual Offences (2019) -- Subject Index -- Author Index.